Alpha-band oscillations track the retrieval of precise spatial representations from long-term memory - Sutterer, David W. (J Neurophysiol, 2019)
A hallmark of episodic memory is the phenomenon of mentally reexperiencing the details of past events, and a well-established concept is that the neuronal activity that mediates encoding is reinstated at retrieval. Evidence for reinstatement has come from multiple modalities, including functional magnetic resonance imaging and electroencephalography (EEG). These EEG studies have shed light on the time course of reinstatement but have been limited to distinguishing between a few categories. The goal of this work was to use recently developed experimental and technical approaches, namely continuous report tasks and inverted encoding models, to determine which frequencies of oscillatory brain activity support the retrieval of precise spatial memories. In experiment 1, we establish that an inverted encoding model applied to multivariate alpha topography tracks the retrieval of precise spatial memories. In experiment 2, we demonstrate that the frequencies and patterns of multivariate activity at study are similar to the frequencies and patterns observed during retrieval. These findings highlight the broad potential for using encoding models to characterize long-term memory retrieval. NEW & NOTEWORTHY Previous EEG work has shown that category-level information observed during encoding is recapitulated during memory retrieval, but studies with this time-resolved method have not demonstrated the reinstatement of feature-specific patterns of neural activity during retrieval. Here we show that EEG alpha-band activity tracks the retrieval of spatial representations from long-term memory. Moreover, we find considerable overlap between the frequencies and patterns of activity that track spatial memories during initial study and at retrieval.